Adolescent perspectives on the effect of cooperative classroom learning on social networks and health. - Benjamin P L Meza; Lee Simões; Gery Ryan; Marisa Saunders; Kristina Turley; Rebecca N Dudovitz; Mitchell D Wong (PLoS ONE)
Cooperative learning is a small-group pedagogical technique hypothesized to impact health by altering classroom social dynamics. Using a grounded theory approach, we performed semi-structured interviews with a purposive sample of twelve students at a large urban public high school and explored the effect of cooperative learning on social networks and health. Students emphasized the social risk inherent in group activities and juxtaposed this with the fostering of social-emotional skills, stronger social networks, and protective factors for health. Shy or socially isolated students described significant social anxiety which cooperative learning techniques helped to curtail. These findings highlight the salience of group learning, its effect on adolescent social dynamics, and its potential for influencing health and well-being.